Designing a European unemployment insurance scheme - László Andor; Sebastian Dullien; H. Xavier Jara; Holly Sutherland; Daniel Gros; Ansgar Belke (Intereconomics, 2014)
With disparities in national unemployment rates reaching record levels, the debate on fiscal stabilisers in Europe has gained new momentum. Can a European unemployment insurance scheme help to absorb asymmetric shocks and bring about the desired level of macroeconomic stabilisation? What should such an unemployment benefit system look like? The contributions to this Forum explore the benefits expected from a European unemployment insurance scheme and discuss the difficulties in establishing such a policy.
Keywords: 330; Arbeitslosenversicherung; Rechtsangleichung; Internationale Wirtschaftspolitik; Konjunktur; Schock; Wirkungsanalyse; EU-Staaten